2020
DOI: 10.1097/jom.0000000000001868
|View full text |Cite
|
Sign up to set email alerts
|

A Mediterranean Lifestyle Is Associated With Lower Hypertension Prevalence and Better Aerobic Capacity Among New England Firefighter Recruits

Abstract: Objective: Examine the association between healthy Mediterranean lifestyle practices and cardiovascular disease (CVD) risk factors among New England firefighter recruits. Methods: A MEDI-Lifestyle score was used to measure adherence to a Mediterranean lifestyle (not smoking, increased physical activity, high adherence to Mediterranean diet, non-obese body mass index, decreased screen time, adequate nightly sleep, and napping) among the recruits. MEDI-Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…This would allow evidence-based clinical follow up and referral for those who might benefit from timely and individualized pharmacological and/or non-pharmacological therapies, thus avoiding expensive high complexity procedures, and promoting a better quality of life. Our data extend previous literature findings 56 , 57 that support early and continuous implementation of healthy lifestyle strategies based on physical activity/fitness promotion and good quality diets as well 58 .…”
Section: Discussionsupporting
confidence: 89%
“…This would allow evidence-based clinical follow up and referral for those who might benefit from timely and individualized pharmacological and/or non-pharmacological therapies, thus avoiding expensive high complexity procedures, and promoting a better quality of life. Our data extend previous literature findings 56 , 57 that support early and continuous implementation of healthy lifestyle strategies based on physical activity/fitness promotion and good quality diets as well 58 .…”
Section: Discussionsupporting
confidence: 89%
“…It seems that increased adherence rates to a Mediterranean diet and healthy lifestyles are consistently related to lower body composition levels. It was even suggested that combining several healthy lifestyle habits could produce synergistic benefits, which we saw with the civilians in our study 6 …”
Section: Discussionmentioning
confidence: 51%
“…It was even suggested that combining several healthy lifestyle habits could produce synergistic benefits, which we saw with the civilians in our study. 6 With the diet and circuit training intervention, we also observed a decrease in BP in both groups. This change is supported by Barnard et al, 12 who found that a Mediterranean diet was better able to reduce SBP and DBP than a low-fat vegan diet.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For 8 weeks, we evaluated the effect of increasing the intensity of response speed and In the studies conducted in the vocational field, in addition to the physical fitness, it is seen that the level of physical fitness of the vocational officers during the study period has turned into a positive relationship as a result of the trainings (Lan et al, 2020). Peterson et al periodic training program findings for different occupational groups reported by, these training studies suggest that different training programs may be a better alternative to periodization programs for occupational groups in order to improve conditioning parameters (Peterson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%